Effects of Conocarpus lancifolius and crocin on superoxide dismutase and protein kinase B genes and protein expressions in diabetic rats. - Mohamed Lotfy; Abdallah Khalaf; Faisal AlBarghouthy; Abdulla Alhashmi; Hesham Adam; Abdulla Almesmari; Biduth Kundu; Taoufik Ksiksi (PLoS ONE)
Background Diabetes mellitus, characterized by chronic hyperglycemia, is a global health challenge. Effective management strategies often focus on improving insulin sensitivity and enhancing antioxidant defenses to mitigate diabetes-related complications. This study explored the therapeutic potential of Conocarpus lancifolius (Co) and crocin in modulating insulin signaling and antioxidant gene expression in diabetic rats. Methods Male Wistar rats were rendered diabetic via alloxan injection and treated orally with C. lancifolius and crocin. Control groups included normal healthy control and untreated diabetic rats. Insulin signaling pathways were assessed by measuring key markers such as protein kinase B (AKT) through western blot and RT-PCR analysis. Antioxidant gene expressions, including superoxide dismutase (SOD), were quantified to evaluate oxidative stress response. Results C. lancifolius and crocin treatment significantly improved fasting blood-glucose levels and insulin sensitivity in diabetic rats. Notably, C. lancifolius and crocin administration resulted in the upregulation of AKT, promoting glucose uptake in peripheral tissues. Additionally, C. lancifolius and crocin increased the expression of the SOD gene, improving antioxidant defense in diabetic rats. Discussion C. lancifolius and crocin had a dual beneficial effect on diabetic rats by modulating key components of the insulin signaling pathway and bolstering antioxidant defenses. The upregulation of AKT as a key gene in insulin signaling pathways suggests an improvement in insulin sensitivity, which is crucial for glycemic control. Concurrently, the elevated antioxidant SOD gene expression indicates reduced oxidative stress, which is vital for preventing diabetic complications. Conclusion Our findings demonstrate that C. lancifolius and crocin significantly improved glucose tolerance, reduced fasting blood glucose levels, and enhanced antioxidant defense in diabetic rats. Histopathological improvements in the pancreas, liver, kidney, and heart further highlight their protective effects against diabetes-induced tissue damage. Additionally, the upregulation of SOD and AKT at both gene and protein levels suggests a role in modulating oxidative stress and insulin signaling pathways. While promising, further studies are needed to clarify their molecular mechanisms, particularly regarding insulin receptor interaction. These findings support the use of C. lancifolius and crocin as natural adjunct therapies to enhance diabetes treatment outcomes.